Security standard compliance and continuous verification for Industrial Internet of Things. (June 2020) - Bicaku, Ani; Tauber, Markus; Delsing, Jerker
Due to globalization and digitalization of industrial systems, standard compliance is gaining more attention. In order to stay competitive and remain in business, different sectors within industry are required to comply with multiple regulations. Compliance aims to fulfill regulations by including all measures imposed by laws and standards. Every device, application, or service implements several technologies at many levels, and standards support interoperability across them. They help to create global markets for industries and enable networked development in order to be successful and sustainable. This work highlights the importance of standard compliance and continuous verification in industrial Internet of Things and implements an automatic monitoring and standard compliance verification framework. In this work, we focus on security, safety, and organizational aspects of industrial Internet of Things. We identify a number of standards and best practice guidelines, which are used to extract security, safety, and organizational measurable indicator points. In addition, a metric model is provided that forms the basis for the necessary information needed for compliance verification, including requirements, standards, and metrics. Also, we present the prototype of the monitoring and standard compliance verification framework used to show the security compliance of an industrial Internet of Things use case.